Conceptualizing Curriculum and Development Theories for Sports Development In Nigeria (2017)
Curriculum theory is a way of describing the educational philosophy of certain approaches to the development and enactment of curriculum. Within the broad field of curriculum studies, it is both a historical analysis of curriculum and a way of viewing current educational curriculum and policy decisions. Development theory, on the other hand, focuses on an assortment of alternative theories and on how societal changes can best be realized. As a result, a multitude of approaches form the basis of these development theories. It is the quest for desirable sport development due to poor performance of the nation's athletes in international meets, poor funding and management of sport, inaccessibility, affordability, usability and poor maintenance of sport and recreational facilities in Nigeria necessitated this expository article. The researchers looked at the existing propounded theories, relate it to sport development and as well as the workability of the theories in bringing about the desired sport development. The curriculum theories looked at those propounded by humanist (or mental disciplinarians), social efficiency, developmentalist (or child study), and social meliorists while the following development theories are also x-rayed upon. Based on the knowledge gained from the propounded theories the following recommendations were made for sport development in Nigeria